2018
DOI: 10.1007/s10592-018-1119-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and cryptic population re-establishment: management implications for the Bojer’s skink (Gongylomorphus bojerii)

Abstract: Understanding genetic structure and diversity underpins the management of isolated populations. Small populations confined to islands may require effective genetic management for population persistence due to inbreeding and reduced genetic diversity. Endemic to the offshore islands of mainland Mauritius, the Bojer's skink (Gongylomorphus bojerii) has previously been managed as two genetic units due to divergence between populations to the north and southeast. In 2009, a few individuals were discovered on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…This is not uncommon in island species and populations have been known to successfully recover from a very small number of individuals (Copsey et al., 2018), for example, the Pink Pigeons went from nine or 10 individuals in 1990 to 446 in 2011 (Swinnerton et al., 2004), the Echo Parakeet Psittacula eques went from as low as 12 individuals in the 1990s to more than 500 in 2010 (Raisin et al., 2012) and the Rodrigues Warbler Acrocephalus rodericanus started with approximately 17 individuals in 1979 and grew to more than 3000 in 2010 (Copsey et al., 2018; Showler et al., 2002). Additional isolated populations may be useful for rescue measures and to protect against localised extinction (du Plessis et al., 2019; Frankham et al., 2019; Grant et al., 2001); however, reliable information and regular assessment of genetic variability are essential for conservation decisions and to monitor whether new populations are successfully established (Gregory et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is not uncommon in island species and populations have been known to successfully recover from a very small number of individuals (Copsey et al., 2018), for example, the Pink Pigeons went from nine or 10 individuals in 1990 to 446 in 2011 (Swinnerton et al., 2004), the Echo Parakeet Psittacula eques went from as low as 12 individuals in the 1990s to more than 500 in 2010 (Raisin et al., 2012) and the Rodrigues Warbler Acrocephalus rodericanus started with approximately 17 individuals in 1979 and grew to more than 3000 in 2010 (Copsey et al., 2018; Showler et al., 2002). Additional isolated populations may be useful for rescue measures and to protect against localised extinction (du Plessis et al., 2019; Frankham et al., 2019; Grant et al., 2001); however, reliable information and regular assessment of genetic variability are essential for conservation decisions and to monitor whether new populations are successfully established (Gregory et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study revealed unique genetic variation at one locality (Perseverance) suggesting additional habitat protection at this site is important for conserving genetic diversity in this species (Tarr & Fleischer, 1999). Re‐introduction of the Grenada Dove to dry forest in its northern historic range, using individuals from both Mt Hartman and Perseverance, could also be beneficial as geographically separate populations are not only important for promoting genetic diversity (du Plessis et al., 2019; Gregory et al., 2012; Major et al., 2021) but also in safeguarding against natural disasters such as hurricanes. Given recent habitat loss on Grenada, availability of suitable habitat on the island for establishing new populations is limited and would likely result in additional isolated populations (Prugh et al., 2008; Rusk et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human beings can affect the genetic structure of populations by introducing or removing barriers and obstacles and preventing or facilitating gene flows. Nevertheless, isolation prevents genetic diversity (which would contribute to the creation of new populations, strategic for conservation) and facilitates inbreeding (du Plessis et al, ). Regulatory activity works in a similar fashion when pushing institutions toward increasing degrees of legal integration and strategic standardization.…”
Section: Weitzman Diversitymentioning
confidence: 99%